Deformation velocity dependence on tensile fracture characteristics of polypropylene injection molding parts. Issue 12 (2nd April 2013) - Ota, Yoshinori; Ito, Hiroshi; Ishikawa, Masaru
<x xml:space="preserve">Abstract</x> To clarify the mechanism of the deformation and fracture in a low‐velocity impact test on the isotactic polypropylene (i‐PP) sheet made by injection molding, the change of the style of fracture and the form of deformation was examined while changing the speed of the striker in a low‐velocity impact test. In the injection molding sheet, an oriented skin layer of some thickness is formed on the surface of the sample sheet. By the stress perpendicular to the orientation direction of the skin layer, crazes were formed easily in parallel with the orientation direction in this layer, and cracks were formed from there. Because these cracks bring the sample sheet a strong restraint of strain, a high stress concentration occurs at the end of this crack even if the formation of the oriented layer is limited on the surface of the sample sheet only, and the low‐velocity impact test leads the sample sheet to a brittle fracture. As a result, the injection molding sheet that forms oriented structure on its surface causes the ductility‐brittleness transform at a lower velocity of deformation compared with the nonoriented sheet. POLYM. ENG. SCI., 53:2659–2665, 2013. © 2013 Society of Plastics Engineers